Is fatigue after work a barrier for leisure-time physical activity? Cross-sectional study among 10,000 adults from the general working population - Bláfoss, Rúni; Micheletti, Jéssica K.; Sundstrup, Emil; Jakobsen, Markus D.; Bay, Hans; Andersen, Lars L. (SAGE Publications, 2018)
Aim: In spite of the many health-related benefits of regular physical activity, fatiguing work may be a barrier to performing leisure-time physical activity. This study investigates the association between work-related fatigue and the duration of low- and high-intensity leisure-time physical activity in workers with sedentary and physically demanding jobs. Methods: From the 2010 round of the Danish Work Environment Cohort Study, currently employed wage earners from the general working population (N=10,427) replied to questions about work-related fatigue (predictor) and duration of low- and high-intensity leisure-time physical activity (outcome). Associations were modelled using general linear models controlling for various confounders. Results: Among workers with physically demanding jobs, higher levels of work-related fatigue were associated with gradually lower levels of leisure-time physical activity – for low, moderate and high levels of work-related fatigue the duration of high-intensity leisure-time physical activity was 133 (95% confidence interval (CI) 127–178), 134 (95% CI 109–160) and 113 (95% CI 86–140) min per week, respectively (trend test p<0.001). The duration of high-intensity leisure-time physical activity was lower among older workers (≥50 years) compared to younger workers (<50 years) (132 ± 126 vs 168 ± 150 min per week) (p<0.0001). Conclusions:The duration of high-intensity leisure-time physical activity gradually decreases with increased work-related fatigue in workers with physically demanding jobs. Older workers perform less high-intensity physical activity than younger workers. Workplaces should consider initiatives to allow workers with physically demanding jobs and older workers to perform physical exercise during working hours and thereby increase physical capacity to meet the job demands.
Keywords: epidemiology; exercise; fatigue; life style; mental fatigue; muscle fatigue; Occupational Health